Sonographic appearance of pediatric omental-containing inguinal hernia: A case report - Derick R. Bunn, BS; Nathan C. Hull, MD; D. Dean Potter, Jr, MD (Radiology Case Reports)
Hemorrhagic, omental-containing inguinal hernia is a very rare cause of acute scrotum in the pediatric population. Here, we describe the case of a 4-year-old boy who presented with acute scrotal swelling and pain. Scrotal ultrasound was used to identify a left indirect inguinal hernia with contents suggestive of inflamed fat and hemorrhagic debris. Laparoscopic inguinal hernia repair and subsequent pathological evaluation confirmed the diagnosis of left indirect inguinal hernia with incarcerated omentum and hemorrhagic ascites. Given the variability of herniated structures in pediatric patients of different ages and sexes, appropriate recognition of hernia contents by ultrasonography is essential for reducing additional imaging studies and accelerating treatment.